The role of infrastructure sustainability and success of construction projects on owner benefits - Thanachon Krajangsri; Jakrapong Pongpeng (My University, 2018)
The infrastructure sustainability and success of construction projects likely influence owner benefits. However, these influences have rarely been examined. Thus, the research aimed to examine such influences and intervening behavior of the success of construction projects between the sustainability of infrastructure and owner benefits using structural equation modeling (SEM). The study finds that there are a direct influence of the sustainability of infrastructure on owner benefits (regression weight: 0.63) and an indirect direct influence of that (regression weight: 0.22) through the intervening role of the success of construction projects. The findings ensure that implementation of infrastructure sustainability projects can enhance the success of construction projects and owner benefits.
Keywords: Construction Project Management and Performance